The Effect of Entrepreneurial Passion and Opportunity Awareness toward the Sustainability of Startup Businesses - Nawir, Caroline Pratiwi; Christiani, Natalia (Universitas Ciputra Surabaya, 2019)
The number of unemployment rate in Indonesia that has been decreasing is caused by the growth of entrepreneurship in Indonesia, which is proven by the number of startup businesses in Indonesia reaching the sixth highest worldwide. Nevertheless, startup businesses have high failure rate, where two of three established startup businesses cannot sustain. With purpose to find out the reason of this phenomenon, this research aims to find out whether entrepreneurial passion and opportunity awareness have significant effects to startup businesses’ sustainability. This research uses the startup businesses of Ciputra University’s 2015 batch students that have been running for minimum 2 years as the sample. These startup businesses are aimed to be able to represent startup businesses since from more than 200 startup businesses established, only 42 startup businesses that sustain. Questionnaires are distributed to the samples using 5-points Likert-scale, and the data collected is then analyzed using Multiple Linear Regression. The result shows that entrepreneurial passion has significant effect toward startup business sustainability, but it does not go the same way with opportunity awareness. Opportunity awareness does not affect significantly toward startup business sustainability since it needs to be converted into opportunity recognition and opportunity exploitation to give significant effects.